GE_GERICHTE C/11956/2014 vom 23. Dezember 2015 - GE Cour de justice (2015)
DIVORCE ; DÉCISION ÉTRANGÈRE ; COMPLÉMENT ; PRÉVOYANCE PROFESSIONNELLE ; DROIT INTERNATIONAL PRIVÉ | CC.122; LDIP.61; LDIP.64; LDIP.15;